The Islam and Global Geopolitics: The Relationship between Religion, Power, and Indonesian International Politics - Kunkunrat , Kunkunrat; Priangani, Ade (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study aims to analyze the relationship between Islam and power dynamics in Indonesian international politics, highlighting how Islamic values ​​interact with national interests and global geopolitical structures. This study begins with a critique of the view that positions religion, particularly Islam, solely as a source of conflict in international relations. Instead, this study views Islam as a normative and strategic element that plays a role in shaping the orientation and practice of Indonesian foreign policy. This study uses a qualitative approach with descriptive-analytical methods. Data were obtained through a literature review of academic books, reputable journal articles, and an analysis of foreign policy documents, official speeches, and diplomatic statements by the Indonesian government. Data analysis was conducted using a content analysis approach to identify patterns of relations between Islamic identity, national interests, and Indonesia's geopolitical strategy. The results show that Islam functions as a source of moral legitimacy and an instrument of soft power in Indonesian foreign policy. This is reflected in the promotion of a moderate Islamic identity (wasathiyah), humanitarian diplomacy, conflict mediation in Muslim countries, and Indonesia's active role in multilateral forums such as the Organization of Islamic Cooperation (OIC). However, Islam's role is contextual and not deterministic. Indonesia continues to prioritize national interests, state sovereignty, and geopolitical rationality, in line with the principles of an independent and active foreign policy. This study concludes that Indonesian foreign policy represents a pragmatic integration of Islamic values, national interests, and global power dynamics. Islam is not positioned as an expansive ideology, but rather as a non-material diplomatic asset that strengthens Indonesia's bargaining position at the regional and international levels.